Suplementa. (O sztuce czytania i nieczytania Podróży zimowej) - Olszański, Grzegorz (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
Stanisław Barańczak collection Journey in Winter (Podróż zimowa) published in 1994 was enthusiastically received by critics, resulting in a great number of related essays and reviews. The author of Supplements reconstructs the main reading strategies of the reviewers and takes a close look at the tools and context they employ. Finally, the reflections on the ways of interpreting the Poznan-born poet’s book provoke the author to consider the critical and poetic biases, the issue of music as a source of identity and a very nonobvious relation between Schubert’s vocal works and the rap aesthetics.